Selection strategy for encapsulation of hydrophilic and hydrophobic ingredients with food-grade materials: A systematic review and analysis - Ruihan Huang; Hongdong Song; Sen Li; Xiao Guan (Food Chemistry: X)
Various lipid and biopolymer-based nanocarriers have been developed to encapsulate food ingredients. The selection of nanocarrier type, preparation techniques, and loading methods should consider the compatibility of nutrient properties, nanocarrier composition, and product requirements. This review focuses on the loading methods for hydrophilic and hydrophobic substances, along with a detailed exploration of nanocarrier categorization, composition, and preparation methods. Both lipid-based and biopolymer-based nanoparticles exhibit the capability to encapsulate hydrophilic or hydrophobic substances. Liposomes and nanoemulsions allow simultaneous encapsulation of hydrophilic and hydrophobic ingredients, while solid lipid nanoparticles and nanostructured lipid carriers are suited for hydrophobic ingredients. The three-dimensional network structure of nanogels can efficiently load hydrophilic substances, while the functional groups in polysaccharides improve the loading capacity of hydrophobic substances through intermolecular interactions. As for protein nanoparticles, the selection of proteins with solubility characteristics analogous to the bioactives is crucial to achieve high encapsulation efficiency.